DCD and DBD lung transplantation optimized by ex vivo perfusion: What to do when the pump fails. Issue 1 (5th November 2019) - Grant, April A.; Bhakta, Shivang; Brozzi, Nicholas; Talon, Andrew; Klima, Alan; Duenas, Alejandro; Galbut, David; Loebe, Matthias; Ghodsizad, Ali
Abstract: Background: Ex vivo perfusion is a safe and feasible method of assessing and using high‐risk donor organs. Aim: We describe a case of successfully ex vivo treated and transplanted human lung allografts. Methods: Donor human lungs were assessed using ex vivo, our trouble shooting protocol allowed safe recovery. Results: We successfully implanted our ex vivo treated organs.